Relationship between Financial Development and Economic Growth in Nigeria: A Triangulation Approach - Judith, Modebe Nwanneka; Chijindu, Ezeaku Hillary (International Journal of Economics and Financial Issues, 2016)
This paper aims at evaluating relation between financial development and economic growth in Nigeria, taking exception from existing literatures by integrating broad distinctive indicators of financial development into our model and using different econometric techniques to assess the finance-growth link between 1987 and 2014. The findings indicate that financial development and economic growth move along together in the long run. It was revealed that credit to the private sector, stock market capitalization and inflation have negative and impact on the economy, while broad money supply, trade openness and foreign direct investment exert positive influence on the economy. The Error correction term in the model availed us the correctional influence in the speed of adjustment which indicated that errors of divergence from equilibrium was corrected at the speed of 86 percent each year. The Granger causality tests show that GDP was granger causal for foreign direct investment, without a feedback system. Keywords: Financial Development, Economic growth, Error Correction Model. JEL Classifications: G10, G18, G20